Windsock mitral valve after prior aortic valve endocarditis - Augustine W. Kang; Hanjay Wang; Diane M. Libert; Gerald J. Berry; Jack H. Boyd (Journal of Cardiothoracic Surgery)
Abstract Background Windsock deformities, though rare, represent a severe form of valvular aneurysm distinguished by localized balloon-like protrusions of the leaflet body. Here, we present a compelling case of windsock mitral valve (MV) formation subsequent to incompletely managed aortic valve (AV) endocarditis. The case is illustrated through radiographic, intraoperative, and histopathologic images. Case presentation We present the case of a 44 year old male patient who presented with symptoms suggestive of infective endocarditis. Despite initiation of appropriate antimicrobial therapy and surgical intervention for AV involvement, the patient developed progressive valvular dysfunction. Subsequent imaging studies revealed the emergence of windsock deformity in the mitral valve apparatus. Intraoperative assessment confirmed the presence of this rare valvular anomaly, which was further corroborated by histopathologic examination. Conclusions We provide, for the first time in the literature, a clear intraoperative view and example of windsock mitral valve (MV) developing after incompletely treated aortic valve (AV) endocarditis.